Flow diversion for internal carotid artery aneurysms with compressive neuro-ophthalmologic symptoms: clinical and anatomical results in an international multicenter study. (18th November 2021) - Boulouis, Gregoire; Soize, Sebastien; Maus, Volker; Fischer, Sebastian; Lobsien, Donald; Klisch, Joachim; Styczen, Hanna; Deuschl, Cornelius; Abdullayev, Nuran; Kabbasch, Christoph; Kaiser, Daniel; Jamous, Ala; et al.
Abstract : Background: Scientific data on the safety and efficacy of flow diverter stents (FDS) for the treatment of unruptured internal carotid artery (ICA) aneurysms with compressive neuro-ophthalmological symptoms are scarce. We studied this subject in a retrospective international multicenter series, pooling data of 9 tertiary care neurointerventional departments. Objective: To investigate, in a retrospective, multicentric cohort of patients presenting with visual or oculomotor symptoms attributed to a compressive carotid artery in an unruptured intracranial aneurysm, the safety and efficacy profiles of FDS, by analyzing neuro-opthalmologic symptom evolution following FDS placement, complications, and aneurysm obliteration rates. Methods: All patients treated since 2015 with a FDS for an unruptured aneurysm of the ICA with signs of compressive cranial nerve symptoms (CN II, III, IV, VI) were included. Results: We treated 55 patients with 55 aneurysms; 21 (38.2%) patients had oculomotor and 15 (27.3%) visual symptoms only; 19 (34.5%) presented with a combination of both. Treatment-related morbidity/mortality occurred in 7.2% and 3.6%, respectively. At last imaging follow-up (13.1±10.5 months) rates of complete aneurysm occlusion, neck remnant, and aneurysm remnant were 72%, 14%, and 14%, respectively. At last clinical follow-up after 13±10.5 months, 19/51 (37.3%) patients had recovered completely and 18/51 (35.3%) had recovered at least partially from their neuro-ophthalmological symptoms. In multivariable models, a longer delay between symptom onset and treatment was associated with higher odds for incomplete recovery and lower odds for any improvement (aOR 1.03 (95% CI 1.01 to 1.07), p=0.047 and 0.04 (0–0.81), p=0.020). Incomplete recovery was independently associated with older age and fusiform aneurysms. Conclusion: FDS are effective to treat patients with compressive aneurysms of the ICA causing neuro-ophthalmological symptoms, especially when treatment is initiated early after symptom onset, and aneurysm occlusion is adequate. However, serious complications are not rare.